Fused Deposition Modelling of Polymer Composite: A Progress - J., Mogan; W. S. W., Harun; K., Kadirgama; D., Ramasamy; F. M., Foudzi; A. B., Sulong; F., Tarlochan; F., Ahmad (MDPI, 2023)
Additive manufacturing (AM) highlights developing complex and efficient parts for various uses. Fused deposition modelling (FDM) is the most frequent fabrication procedure used to make polymer products. Although it is widely used, due to its low characteristics, such as weak mechanical properties and poor surface, the types of polymer material that may be produced are limited, affecting the structural applications of FDM. Therefore, the FDM process utilises the polymer composition to produce a better physical product. The review’s objective is to systematically document all critical information on FDMed-polymer composite processing, specifically for part fabrication. The review covers the published works on the FDMed-polymer composite from 2011 to 2021 based on our systematic literature review of more than 150 high-impact related research articles. The base and filler material used, and the process parameters including layer height, nozzle temperature, bed temperature, and screw type are also discussed in this review. FDM is utilised in various biomedical, automotive, and other manufacturing industries. This study is expected to be one of the essential pit-stops for future related works in the FDMed-polymeric composite study.